Noninvasive prenatal detection of sex chromosomal aneuploidies by sequencing circulating cell‐free DNA from maternal plasma. (17th May 2013) - Mazloom, Amin R.; Džakula, Željko; Oeth, Paul; Wang, Huiquan; Jensen, Taylor; Tynan, John; McCullough, Ron; Saldivar, Juan‐Sebastian; Ehrich, Mathias; van den, Dirk; Bombard, Allan T.; Maeder, Margo; et al.
ABSTRACT Objective Whole‐genome sequencing of circulating cell free (ccf) DNA from maternal plasma has enabled noninvasive prenatal testing for common autosomal aneuploidies. The purpose of this study was to extend the detection to include common sex chromosome aneuploidies (SCAs): [47, XXX], [45, X], [47, XXY], and [47, XYY] syndromes. Method Massively parallel sequencing was performed on ccf DNA isolated from the plasma of 1564 pregnant women with known fetal karyotype. A classification algorithm for SCA detection was constructed and trained on this cohort. Another study of 411 maternal samples from women with blinded‐to‐laboratory fetal karyotypes was then performed to determine the accuracy of the classification algorithm. Results In the training cohort, the new algorithm had a detection rate (DR) of 100% (95%CI: 82.3%, 100%), a false positive rate (FPR) of 0.1% (95%CI: 0%, 0.3%), and nonreportable rate of 6% (95%CI: 4.9%, 7.4%) for SCA determination. The blinded validation yielded similar results: DR of 96.2% (95%CI: 78.4%, 99.8%), FPR of 0.3% (95%CI: 0%, 1.8%), and nonreportable rate of 5% (95%CI: 3.2%, 7.7%) for SCA determination Conclusion Noninvasive prenatal identification of the most common sex chromosome aneuploidies is possible using ccf DNA and massively parallel sequencing with a high DR and a low FPR. © 2013 John Wiley & Sons, Ltd.